Busy nights: High seed dispersal by crickets in a neotropical forest - Santana, Flávia Delgado; Baccaro, Fabricio Beggiato; Costa, Flávia Regina Capellotto (American Naturalist, 2016)
Among invertebrates, ants are the most abundant and probably most important seed dispersers in both temperate and tropical environments. Crickets, also abundant in tropical forests, are omnivores and commonly attracted to fruits on the forest floor. However, their capability to remove seeds has been reported only once. We compared Marantaceae seed removal by crickets and ants to assess the role of crickets as secondary seed dispersers in Amazonia. Compared with ants, crickets dispersed an equivalent number of seeds and tended to disperse larger seeds farther. However, seed removal by crickets occurs mostly at night, suggesting that removal of arillate seeds by crickets on the tropical forest floor is probably being overlooked or wrongly attributed to other invertebrate groups. One potential consequence of seed dispersal by crickets may be a change in the local spatial distribution of arillate-seed species, due to lower aggregation around ant nests. © 2016 by The University of Chicago.
Keywords: Abundance Estimation; Ant; Cricket; Forest Floor; Invertebrate; Neotropical Kingdom; Seed Dispersal; Spatial Distribution; Temperate Environment; Tropical Forest; Amazonia; Formicidae; Gryllidae; Grylloidea; Invertebrata; Marantaceae; Orthoptera; Animals; Ant; Forest; Fruit; Gryllidae; Seed Plant; Seed Dispersal; Animal; Ants; Forests; Fruit; Gryllidae; Seed Dispersal; Seeds